Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1038/ijo.2012.84
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and body weight change in postmenopausal women: results from the Women's Health Initiative

Abstract: Objective: To determine if alcohol consumption is associated with incident overweight or obesity in normal-weight, postmenopausal women. Design: Prospective cohort study considering baseline alcohol consumption and subsequent weight change over 7 years. Subjects: 15 920 normal-weight (BMI: 18.5–24.9 kg/m2), postmenopausal women enrolled in the Women’s Health Initiative clinical trial (WHI CT). Measurements: Body weight change and incident overweight and obesity (BMI, 25.0–29.9 and ≥ 30 kg/m2) over 7 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 34 publications
3
31
0
Order By: Relevance
“…The association between alcohol consumption and BMI has been equivocal in epidemiologic studies (39). In our heterogeneity-corrected analysis, alcohol consumption was negatively associated with BMI among women, as supported by prior work (40,41), but not among men, suggesting possible sex differences. Our findings and those of others (42,43) indicate that marriage is positively associated with BMI.…”
Section: Discussionsupporting
confidence: 73%
“…The association between alcohol consumption and BMI has been equivocal in epidemiologic studies (39). In our heterogeneity-corrected analysis, alcohol consumption was negatively associated with BMI among women, as supported by prior work (40,41), but not among men, suggesting possible sex differences. Our findings and those of others (42,43) indicate that marriage is positively associated with BMI.…”
Section: Discussionsupporting
confidence: 73%
“…After adjusting for many confounders, observational studies have demonstrated a significant correlation between light or moderate alcohol use and reduced risk of several diseases and health problems, as shown in the following list: • Alzheimer's disease/dementia [1][2][3] • Asthma [4] • Autoimmune hypothyroidism [5] • Colorectal cancer [6] • Common cold [7] • Coronary heart disease [8,9] • Diabetes (type 2) [10] • Gallstones [11] • Hearing loss [12,13] • Intermittent claudication [14] • Liver cirrhosis [15] • Low birth weight, prematurity [16] • Lower urinary tract symptoms (in men) [17] • Metabolic syndrome [18] • Negative child development [19][20][21] • Osteoporosis [22][23][24][25] • Overweight [26][27][28] • Psychiatric disorders [29][30][31][32] • Renal cell cancer [33] • Rheumatoid arthritis [34][35][36] • Stroke (ischaemic) [37] • General health status [38,39] • All cancer mortality [40] • Total mortality [41] For the majority of these diseases and health problems, the correlation has been confirmed in more than one study. For seven of these, several studies and metaanalyses have been published...…”
Section: Introductionmentioning
confidence: 99%
“…6 Behaviors responsible for weight gain in old ages have been evaluated in two large study samples. 7,8 In a prospective study of post menopausal women with a 7-year follow-up, those who reported a moderate alcohol intake showed lower weight gain and had less risk of becoming overweight or obese. 7 In a cohort of men aged 65 years at baseline, followed from 1988 to 1998, physical activity was protective against weight gain: 8 subjects enrolled in 70 min/day of moderate intensity physical exercise were able to keep their weight stable over the 10-year follow-up period.…”
mentioning
confidence: 99%